2021
DOI: 10.1002/slct.202004487
|View full text |Cite
|
Sign up to set email alerts
|

Greenwaylactams A, B and C, the First Group of Sesquiterpene Alkaloids with an Eight‐Membered Lactam Ring from Greenwayodendron oliveri

Abstract: Three new sesquiterpene alkaloids of the polyveoline type containing eight‐membered lactam rings named greenwaylactam A (1), B (2) and C (3) were isolated from the leaves of a Cameroonian medicinal plant Greenwayodendron oliveri (Engl.) Verdc along with three known compounds diacetylpolyveoline (4), N‐acetyl‐8α‐polyveolinone (5) and methyl pheophorbide‐A (6). These comprise the first members of a new class of ξ‐lactam sesquiterpenes. Compounds were isolated by means of successive column chromatographies and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…This improved protocol for C-3 acylation should prove useful for the synthesis of potential analogues of these alkaloids. Gratifyingly, all the analytical data of our synthetic natural products were in agreement with the data obtained in the isolation report 4 (largest NMR shift deviation: Δ δ H = 0.05 ppm, Δ δ C = 0.4 ppm, J -values match throughout; melting points: 274 vs. 277 °C for 3 and 247–250 vs. 249–250 °C for 4 , for detailed comparison see ESI†) and total synthesis. 6 Cleavage of the tosyl group before the cyclisation gave rise to 13 , which was examined for a potential N-terminated cyclisation.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This improved protocol for C-3 acylation should prove useful for the synthesis of potential analogues of these alkaloids. Gratifyingly, all the analytical data of our synthetic natural products were in agreement with the data obtained in the isolation report 4 (largest NMR shift deviation: Δ δ H = 0.05 ppm, Δ δ C = 0.4 ppm, J -values match throughout; melting points: 274 vs. 277 °C for 3 and 247–250 vs. 249–250 °C for 4 , for detailed comparison see ESI†) and total synthesis. 6 Cleavage of the tosyl group before the cyclisation gave rise to 13 , which was examined for a potential N-terminated cyclisation.…”
supporting
confidence: 87%
“… 3 In 2021, the antibacterial natural products greenwaylactams A–C (2–4, see Scheme 1 ) were isolated from Greenwayodendron oliveri by Kouam and Tchamgoue. 4 The tetracyclic carbon skeleton incorporating an 8-membered lactam immediately attracted our attention. We anticipated that the potential precursor to this lactam could be accessed with exceeding efficiency through a biomimetic polyene cyclisation 5 of an indole farnesyl derivative.…”
mentioning
confidence: 99%
“…Having successfully prepared all members of the greenwayodendrine family of natural products, we focused our attention on the total synthesis of greenwaylactam A ( 4 ), B ( 23 ) and C ( 24 ). These secondary metabolites were isolated in 2021 by Kouam and Tchamgoue from the Cameroonian medicinal plant Greenwayodendron oliveri and were shown to possess antibacterial activity [9a] . Continuation of our previous screening campaign (Scheme 2B) showed that exposure of epoxide 12 to different Lewis acids at 0 °C or −78 °C affords trans ‐pentacycle 6 b [16] in only 22–27 % NMR yield together with a complex product mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Other activities were reported for diterpene alkaloids, as protective against cardiomyocytes H2O2-induced injurity [103], anti-inflammatory effects against NO production [104]. Kemgni et al (2021) [105] isolate sesquiterpenes alkaloids with an unusual eight-membered lactam ring (4). They were obtained from the leaves of a Cameroonian medicinal plant Greenwayodendron oliveri (Engl.)…”
Section: Alkaloidsmentioning
confidence: 99%